Implications of Civil Law on the Transfer of Land Rights through Deeds Under Hand : An Analysis of the Conformity between the Civil Code and the Principal Agrarian Law - Muslim Muslim (PT. Anagata Sembagi Education, 2025)
The transfer of land rights in Indonesia is an important issue in agrarian law which is colored by normative dualism between the Civil Code (KUHPerdata) and the Basic Agrarian Law (UUPA). The Civil Code recognizes the agreement on the transfer of rights through a deed under hand as long as it fulfills the elements of Article 1320, and considers it valid under civil law and has evidentiary value in accordance with Articles 1874-1880. However, the UUPA as a lex specialis requires that the transfer of land rights is only valid if it is made through an authentic deed by PPAT and registered with the land office. This disharmony creates legal uncertainty, especially in the protection of third parties and certainty of ownership. This study uses a normative juridical method with a historical, systematic, and comparative approach to analyze the applicability of deeds under hand in the Indonesian land law system. The results of the study show that the deed under hand only produces obligatory rights and cannot be the constitutive basis for the transfer of rights. Therefore, harmonization between the Civil Code and the UUPA needs to be carried out in order to realize a coherent, responsive, and guaranteed legal legal system. This reformulation is important to adapt colonial norms to the principles of national law based on justice and certainty.